Comparing the associations between host and tumor factors with survival outcomes with anti‐PD‐1 immunotherapy in metastatic melanoma. (4th August 2022) - Koczka, Kim; Rigo, Rodrigo; Batuyong, Eugene; Cook, Sara; Asad, Mohammad; Vallerand, Isabelle; Suo, Aleksi; Wang, Edwin; Cheng, Tina
Abstract: Background: Anti‐programmed death‐1 (PD‐1) immunotherapy has drastically improved survival for metastatic melanoma; however, 50% of patients have progression within 6 months despite treatment. In this study, we investigated host, and tumor factors for metastatic melanoma patients treated with anti‐PD‐1 immunotherapy. Methods: Patients treated with the anti‐PD‐1 immunotherapy between 2014 and 2017 were identified in Alberta, Canada. All patients had Stage IV melanoma. Patient characteristics, investigations, treatment, and clinical outcomes were obtained from electronic medical records. Results: We identified 174 patients treated with anti‐PD‐1 immunotherapy. At 37.1 months median follow‐up time 135 (77.6%) individuals had died and 150 (86.2%) had progressed. An elevated lactate dehydrogenase (LDH) had a response rate of 21.0% versus 41.0% for those with a normal LDH ( p = 0.017). Host factors associated with worse median progression‐free survival (mPFS) and median overall survival (mOS) included liver metastases, >3 sites of disease, elevated LDH, thrombocytosis, neutrophilia, anemia, lymphocytopenia, and an elevated neutrophil/lymphocyte ratio. Primary ulcerated tumors had a worse mOS of 11.8 versus 19.3 months ( p = 0.042). We identified four prognostic subgroups in advanced melanoma patients treated with anti‐PD‐1 therapy. (1) Normal LDH with <3 visceral sites, (2) normal LDH with ≥3 visceral sites, (3) LDH 1‐2x upper limit of normal (ULN), (4) LDH ≥2x ULN. The mPFS each group was 14.0, 6.5, 3.3, and 1.9 months, while the mOS for each group was 33.3, 15.7, 7.9, and 3.4 months. Conclusion: Our study reports that host factors measuring the general immune function, markers of systemic inflammation, and tumor burden and location are the most prognostic for survival. Abstract : Kaplan–Meier curve of performance‐free survival of cutaneous and melanoma of unknown primary patients stratified by prognostic criteria. LDH, lactate dehydrogenase; mPFS, median performance survival; ULN, upper limit of normal.